Posidonia oceanica banquette accumulations in southern Catalonia: management approaches and key parameters for coastal protection - Astudillo-Gutierrez, Carlos; Pavo-Fernandez, Eva; Gracia, Vicente; Sierra, Joan Pau; Llull, Toni; Mosso, Cesar; Sanchez-Artus, Xavier; Sanchez-Arcilla, Agustín (Frontiers in Marine Science, 2025)
Seagrass banquettes, formed primarily by Posidonia oceanica, play a critical role in coastal protection and sediment dynamics. However, due to their perceived negative impact on seaside tourism, local authorities frequently remove these accumulations using heavy machinery, contributing to beach erosion. This study surveyed a 100 km stretch of the southern Catalan coastline to map the spatial distribution of Posidonia oceanica banquettes and to investigate their relationship with adjacent submerged seagrass meadows. The results indicate that banquette development is most prevalent in meadows with a depth of less than 5 m, under local wave conditions with significant wave heights ranging from 0.4 to 0.8 m. Pixavaques Beach was selected as a case study to evaluate the physical characteristics and ecological functions of banquettes. Granulometric and permeability analyses were conducted on sand and banquette samples, alongside in situ penetration resistance measurements. The results indicate that banquettes located near the shoreline accumulate around 12 times less sediment than those located further inland, primarily due to their continuous exposure to wave action, which produces a natural washing and removal of sediments. The mean permeability values of the banquette were 16.41 cms− 1 in the zones closest to the shoreline and 0.32 cms− 1 at a distance of 1.5 m inland. The values obtained for these samples were higher than those measured in bare sand (0.05 cms− 1). The maximum in situ penetration resistance values were recorded as 1.84 MPa in bare sand and 1.68 MPa in the banquettes. The highest values measured within the banquettes indicate zones of greater sediment accumulation. Additionally, the artificial nourishment implemented to counteract erosion from banquette removal has led to increased grain size and steeper beach profiles. These findings highlight the protective function of banquettes and support alternative, sustainable management strategies, such as repositioning or partial retention, that balance ecological integrity with the demands of coastal tourism.